Hidup Layak Dalam Perspektif Ekonomi Syariah - irfan Djufri; Rahman Ambo Masse; Misbahuddin Misbahuddin (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2023)
The purpose of this study is to find out how the concept of a decent/prosperous life is in Islamic economics. The research method used is literature research. Data collection techniques come from different literature, then use a normative descriptive approach and are analyzed according to problems related to the topic and title of the research paper. The results of his research are the concept of Islamic economics, as well as the principles of Islamic economics and the concept of a decent life in Islam.